VetSet2Go : a collaborative outcomes and assessment framework building employability, resilience and veterinary graduate success. Final report 2019. - Cake, Martin; Bell, Melinda; Cobb, Kate; Feakes, Adele; Hamood, Wendy; Hughes, Kirsty; King, Eva; King, Laura; Mansfield, Caroline; McArthur, Michelle; Matthew, Susan; Mossop, Liz; et al. (Australia. Dept of Education, 2019)
VetSet2Go was a three-year project that ran from September 2015 through to August 2018. It aimed to explore what employability means in the veterinary context; develop an evidence-based, multi-stakeholder framework of the capabilities most important for employability and success in the veterinary profession; and create aligned assessment tools and resources to build these capabilities, in order to improve veterinary graduate employability, resilience in transition to practice, and professional satisfaction and success. Scoping reviews and research subprojects converged to inform a Delphi consensus process and an inaugural Veterinary Employability Forum held in February 2017. The project initiated a body of new research from multiple stakeholder perspectives, which was distilled to inform an evidence-based framework. The VetSet2Go framework consists of 18 capabilities within five broad, overlapping domains: psychological resources (for the self), effective relationships (for others), veterinary capabilities (for the task), professional commitment (for the mission) and self-awareness (for the central process).